ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN MEMAKAI ALAT PELINDUNG TELINGA PADA TENAGA KERJA BAGIAN PRODUKSI DI PT. TOTAL DWI DAYA SEMARANG TAHUN 2014 (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2015)
This research was a descriptive research with cross sectional approach. The population in this study are all part of the production workforce by 24 respondents. Total sampling is a sampling technique in this study. Instrument in this study is a questionnaire interview guide. Data analysis was performed using univariate and bivariate (Î± = 0.05). The results showed that there is a relationship between attitudes and compliance with wearing comfort hearing protection (p value = 0.009), (p value = 0.033). There is no relationship between knowledge, motivation, and supervision of compliance with wearing hearing protection (p value = 0615), (p value = 0.092), (p value = 0.326). Advice given to companies that should do the monitoring work schedule and the labourer must have hearing protection at working, for workers who are already safe behavior should be maintained so that workers are expected to influence attitudes work became obedient adherence.